일부 치위생과 학생의 수업방법선택에 따른 성취목표성향과 학업성취도의 관계 - 신애리(Ae-Ri Shin); 하명옥(Myung-Ok Ha) (한국콘텐츠학회 논문지, 21(12), 2021)
A study was conducted to identify the general characteristics of some dental hygiene students and to identify the factors affecting the achievement goal orientation and academic achievement according to the teaching method selection for increase the academic achievement of the subject in the special education environment caused by the COVID-19. In the second semester of 2020, a survey was conducted on 122 students of G University's dental hygiene department located in Gwangju, and the general characteristics and achievement goal orientation were surveyed. Academic achievement has used the midterm and final exam scores and the collected data were analyzed using Kruskal-Wallis test, Mann-Whitney U test, Pearson's correlation test, Multiple Linear Regrission. According to the general characteristics, there was a significant difference in subject understanding, subject interest, and subject satisfaction, and learning satisfaction showed a strong correlation with the completion goal tendency. There was a significant difference in academic achievement according to the class choice, and the factor that influenced the academic achievement was the case that the teaching method was chosen face-to-face. Therefore, in order to improve learners' academic achievement, it is necessary to increase the proportion of face-to-face classes and to establish an effective lesson plan that can increase the degree of subject understanding, subject interest, and subject satisfaction. 코로나-19의 유행으로 비대면수업의 비중이 늘어나는 특수교육환경 속에서 대상자의 학업성취도를 높이기 위한 방안을 마련하고자 일부 치위생과 학생들을 대상으로 일반적 특성을 파악하고 수업방법선택에 따른 성취목표성향과 학업성취도에 영향을 미치는 요인을 확인하는 연구를 실시하였다. 2020년 2학기 광주광역시 소재의 G대학 치위생과 학생 122명을 대상으로 일반적 특성, 성취목표성향은 설문조사를 실시했고 학업성취도는 중간시험과 기말시험 점수를 사용했으며 수집된 자료는 Kruskal-Wallis test와 Mann-Whitney U test, Pearson's correlation test, Multiple Linear Regrission으로 분석하였다. 일반적 특성에 따른 완숙목표성향은 교과목이해도, 교과목흥미도, 학과만족도에 유의한 차이를 보였고(p<0.01) 학과만족도는 완숙목표성향에 강한 상관관계를 나타냈다(p<0.01). 수업선택에 따라 학업성취도는 유의한 차이를 보였고(p<0.01), 학업성취도에 영향을 주는 요인은 수업방법을 대면으로 선택한 경우였다(p<0.05). 따라서 학습자의 학업성취도를 향상하기 위해 대면수업의 비중을 늘리고 수업에 대하여 완숙목표성향을 지향할 수 있도록 교과목이해도, 교과목흥미도, 학과만족도를 높일 수 있는 효율적인 수업계획을 세우는 것이 필요할 것이다.